Grip and load force coordination in cyclical isometric manipulation task is not affected by the feedback type - Pedão, Sabrina Tiago; Barela, José Angelo [UNESP]; De Almeida Lima, Kauê Carvalho; De Freitas, Paulo Barbosa (Springer Nature, 2013)
Background: The relationship between normal and tangential force components (grip force - GF and load force - LF, respectively) acting on the digits-object interface during object manipulation reveals neural mechanisms involved in movement control. Here, we examined whether the feedback type provided to the participants during exertion of LF would influence GF-LF coordination and task performance. Methods. Sixteen young (24.7 ±3.8 years-old) volunteers isometrically exerted continuously sinusoidal FZ (vertical component of LF) by pulling a fixed instrumented handle up and relaxing under two feedback conditions: targeting and tracking. In targeting condition, FZ exertion range was determined by horizontal lines representing the upper (10 N) and lower (1 N) targets, with frequency (0.77 or 1.53 Hz) dictated by a metronome. In tracking condition, a sinusoidal template set at similar frequencies and range was presented and should be superposed by the participants' exerted FZ. Task performance was assessed by absolute errors at peaks (AEPeak) and valleys (AEValley) and GF-LF coordination by GF-LF ratios, maximum cross-correlation coefficients (r max), and time lags. Results: The results revealed no effect of feedback and no feedback by frequency interaction on any variable. AE Peak and GF-LF ratio were higher and rmax lower at 1.53 Hz than at 0.77 Hz. Conclusion: These findings indicate that the type of feedback does not influence task performance and GF-LF coordination. Therefore, we recommend the use of tracking tasks when assessing GF-LF coordination during isometric LF exertion in externally fixed instrumented handles because they are easier to understand and provide additional indices (e.g., RMSE) of voluntary force control. © 2013 Pedão et al.; licensee BioMed Central Ltd.
Keywords: Auditory; Hand function; Motor control; Visual; adult; analysis of variance; biomechanics; feedback system; female; hand strength; human; male; muscle isometric contraction; physiology; pressure transducer; psychomotor performance; statistical analysis; weight bearing; Adult; Analysis of Variance; Biomechanics; Data Interpretation, Statistical; Feedback, Physiological; Female; Hand Strength; Humans; Isometric Contraction; Male; Psychomotor Performance; Transducers, Pressure; Weight-Bearing; Young Adult